Supporting data for the article: Advances in design of high-performance heterostructured scintillators for Time-of-Flight Positron Emission Tomography - Bizarri, Gregory (Cranfield University, 2024)
Data associated with Advances in design of high-performance heterostructured scintillators for Time-of-Flight Positron Emission Tomography
Keywords: 'radiation detection'; 'ultra fast timing'; 'heterostructured scintillator'; 'time of flight positron emission tomography'